Pengaturan Tempat Duduk untuk Meningkatkan Motivasi Belajar Bahasa Inggris Siswa Kelas IX TA2 MTs. Nurul Jadid: Penelitian - Soleha, A. T.; Suryanto, B. T.; Ustman, M. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to increase students' motivation to learn English through the application of various seating arrangements in class IX TA2 MTs. Nurul Jadid Paiton, Probolinggo. This study uses the Classroom Action Research (CAR) method, which is carried out in two cycles, where each cycle consists of the planning, action, observation, and reflection stages. The research subjects consisted of 26 female students, all of whom were Islamic boarding school students. The data collection instruments consisted of observation sheets, a learning motivation questionnaire with a 1–5 Likert scale based on the ARCS model (attention, relevance, confidence, satisfaction), and field notes. In the pre-cycle, student motivation was still low with an average score of 50.2. After implementing the U-shape seating arrangement in cycle I, the motivation score increased to 65.7. Improvements in learning strategies in cycle II, which focused on collaborative interaction, resulted in a more significant increase in motivation with an average score of 72.8. These findings indicate that U-shape seating arrangements can create an interactive learning atmosphere, increase confidence, and encourage active student participation in English language learning. Thus, classroom management strategies through seating variations can be implemented as an effective solution for teachers in their efforts to increase student learning motivation.